The relationship between serum levels of CA 125 and the degree of differentiation in ovarian neoplasms - Eduardo Cambruzzi; Rosane de Lima; Simone Luís Teixeira; Karla Lais Pêgas (Sociedade Brasileira de Patologia Clínica, 2014)
Introduction: Primary ovarian neoplasms exhibit a wide range of histopathological aspects, and tumors with epithelial differentiation are the most frequent. Among the malignant tumors, the most common histological type corresponds to serous adenocarcinoma, whose diagnosis is established in advanced stages of the disease in approximately 75% of the patients. Tumor marker CA 125 represents a glycoprotein synthesized mainly by neoplastic cells with epithelial differentiation, and its serum level seems to be associated with the biological potential of these lesions. Objective: To estimate the association between serum levels of CA 125 and the degree of differentiation in primary ovarian neoplasms. Method: Sixty distinct cases of primary ovarian tumors were selected, previously analyzed at the Laboratory of Pathology of the Hospital Complex of Universidade Luterana do Brasil (Ulbra), between 2005 and 2010, from patients undergoing concomitant analysis of CA 125. In each case, age, tumor size, histological type, degree of differentiation, presence of necrosis and tumor invasion of the albuginea or extraovarian tissues, pathological stage and serum CA 125 were determined. Results: A statistically significant relationship between CA 125 levels and histological grade (p = 0.001), age (p = 0.009), biological behavior of the tumor (malignant or benign - p = 0.002) and extraovarian invasion (p = 0.005) was found. No relationship between CA 125 levels and tumor size (p = 0.1006) and pathologic stage (p = 0.1) was determined. Histologic grade was associated with the presence of necrosis (p = 0.001), extraovarian invasion (p = 0.009) and tumor size (p = 0.008). Conclusion: In the present study, serum levels of CA 125 were associated with histological grade in primary ovarian neoplasms, especially in high-grade malignant tumors, suggesting that high levels of this glycoprotein are associated with lesions of more aggressive biological behavior.